Accumulation, Composition, Density, and Volume of Marine Litter on Palu Bay (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
Marine litter poses an increasing threat to the coastal ecosystem of Palu Bay, Indonesia, driven by contrasting land-based human activities. This study assessed the accumulation, composition, density, and volume of macro-debris (>2.5 cm) at four coastal stations representing residential, river-influenced, and tourism-dominated areas. Surveys were conducted from June to September 2025 using a line transect method. The results showed marked spatial differences in marine litter characteristics. Residential and river-influenced sites (Baiya and Mamboro Beaches) recorded the highest debris weights (4003.67–4378.22 g/m²), dominated by heavier household waste transported via river systems. In contrast, tourism areas (Taman Ria and Kampung Nelayan Beaches) exhibited lower debris weights (1697.67–1892.37 g/m²) but significantly higher item densities (14.46–17.28 items/m²) and volumes, reflecting the dominance of lightweight, single-use plastics from recreational activities. Plastic debris dominated all stations, exceeding 94% in tourism zones. These findings demonstrate a clear dichotomy in litter sources and characteristics between tourism and residential areas, underscoring the need for targeted management strategies. Effective mitigation should prioritize single-use plastic restrictions, adequate waste facilities, and visitor awareness in tourism areas, alongside improved household waste collection and riverine waste control in residential watersheds. Such source-specific approaches are essential for sustainable coastal management in Palu Bay and comparable semi-enclosed bays.
Keywords: Marine debris; Macro-plastic; Coastal pollution; Waste management; Palu Bay